ANALISIS PENERAPAN PSAK NO.102 ATAS PEMBIAYAAN MURABAHAH PADA PT. BANK SYARIAH MANDIRI CABANG MANADO - Muklis, Sri Wahyuni; Pangemanan, Sifrid Sonny; Mawikere, Lidia (GOING CONCERN : JURNAL RISET AKUNTANSI, 2013)
Funding product â€œMurabahahâ€ is one of upscale for syariah banking. IAI (Indonesia Accountant Association) has published Accountant funding standard statement (PSAK) No. 102, which admission, transparency, measuring and explanation from â€œMurabahahâ€ transaction. the other purpose from this research is to know adjustment of â€œMurabahahâ€ in PT. Bank Syariah Mandiri, Manado Branch with PSAK No. 102. Descriptive theory is been used for this research, which is the data has been gathered, arranged, interpret, and analysed, so it can give full information or picture about â€œMurabahahâ€ funding in PT. Bank Syariah Mandiri, Manado Branch, where this presentation has been standardized based from standard accountant funding statement No. 102.